(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Two-dimensional (2D) nanostructures are the focal point of their plasmonic resonances that are the foundation for modern nanophotonics to manipulate and localize light on a sub-diffraction regime. Such types of resonances are the foundation for several potential applications including ultra-sensitive biosensors, energy-harvesting technology, and photonic integrated platforms. Heretofore, it has been feasible to investigate implications only within idealized Hermitian models of lossless and gainless regimes and thus on the naturally non-Hermitian interactions of actual nanoscale systems. This has constrained the predictive power of theory and slowed productive progress in the design of plasmonic devices. This asymmetry is dealt with here in careful examination of spectral plasmonic resonance properties and stability in 2D nanostructures’ non-Hermitian physics. Notable is a resonance frequency shift, linewidth variation, and exceptional points (EPs)—singularities with special non-Hermitian behavior and direct technological relevance. From advanced finite-difference time-domain (FDTD) simulations, the work accurately follows nanoscale electromagnetic coupling and yields quantitative descriptions of eigenmode coupling processes. We find that non-Hermitian effects cause dramatic wavelength shifts of resonances and staggering colossal local field amplifications at EPs far greater than those of their Hermitian counterparts. This paves the way to ultra-sensitive optical sensing, ultra-efficient energy-harvesting performance, and optimal design of integrated photonic circuits. By bridging the gap between idealized theoretical descriptions and nanoscale physics, the book gives not only profound insight into non-Hermitian plasmonics but also a platform for next-generation nanophotonic devices.